Biosensors, Biomarkers and Biometrics: a Bootcamp Perspective. (14th August 2020) - James, Osian P; Robinson, David B T; Hopkins, Luke; Bowman, Chris; Powell, Arfon G M T; Brown, Chris; Bailey, Damian M; Egan, Richard J; Lewis, Wyn G
Abstract : Introduction: Competitive physical performance is routinely monitored by wearable technology (biosensors), yet professional healthcare is not, despite high prevalence of trainee stress and burnout, notwithstanding the corresponding risk to patient safety. This study aimed to document the physiological stress response of UK Core Surgical Trainees (CSTs) during simulation training. Methods: CSTs (n=20, 10 male) were fitted with Vital Scout Wellness Monitors (VivaLNK, Campbell, California, USA) for an intensive 3-day training bootcamp. In addition to physiological parameters, CST demographics, event diaries and Maslach Burnout Inventory scores were recorded prospectively during exposure to three scenarios: interactive lectures, clinical skills simulation and non-technical (communication) training. Results: Baseline heart rate (BHR, 60 bpm (range 39–81 bpm)) and baseline respiratory rate (14/min (11–18/min)) varied considerably and did not correlate (rho 0.076, p=0.772). BHR was associated with weekly exercise performed (66 bpm (<1 hour) vs 43 bpm (>5 hour), rho −0.663, p=0.004). Trainee response (standardised median heart rate vs BHR) revealed heart rate was related proportionately to lectures (71 bpm, p<0.001), non-technical skills training (79 bpm, p<0.001) and clinical skills simulation (88 bpm, p<0.001). Respiratory rate responded similarly (p<0.001 in each case). Heart rate during clinical skills simulation was associated with emotional exhaustion (rho 0.493, p=0.044), but maximum heart rate was unrelated to CSTs' perceived peak stressors. Discussion: Stress response, as derived from positive sympathetic heart rate drive varied over two-fold, with a direct implication on oxygen uptake and energy expenditure, and highlighting the daily physical demands placed upon clinicians.